Environmental Sanitation Challenges and Opportunities in Indonesia Coastal Regions: A Review - Abdul Rahman; Andi Isnaeni (Journal of Epidemiology and Health Science, 2025)
Background: Coastal areas present distinct challenges and characteristics that differentiate them from inland regions. These include issues related to substandard housing, limited access to healthcare services, and environmental factors that contribute to both economic and public health problems. Environmental sanitation is a critical component, as poor sanitation in coastal communities often leads to increased vulnerability to disease and reduced quality of life. Monitoring environmental factors that influence human health is essential in these regions, where infrastructure and services are frequently inadequate. Objective: This study aims to provide a comprehensive overview of environmental sanitation conditions in coastal areas of Indonesia. Methods: A Systematic Literature Review (SLR) approach was employed to collect and analyze relevant scholarly articles from online databases, particularly Google Scholar and ResearchGate. The selection process followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Articles published between 2020 and 2024 were included, using keywords such as "sanitation," "environment," and "coastal." The analysis focused on identifying the status, challenges, and determinants of sanitation practices in coastal communities across Indonesia. Results: The findings from the reviewed literature indicate that basic environmental sanitation in Indonesia's coastal regions remains below national health standards. Common issues identified include the lack of proper latrine facilities, poor access to clean water, inadequate waste and wastewater management systems, and suboptimal community hygiene practices. These conditions are influenced by several contributing factors, such as low levels of public knowledge, limited economic capacity, and poor environmental infrastructure. Conclusion: The review concludes that environmental sanitation challenges in Indonesia’s coastal areas are significantly influenced by factors including community knowledge, income level, and ingrained behavioral practices. Long-standing cultural habits, passed down through generations, have resulted in insufficient attention to proper sanitation practices, thereby increasing susceptibility to preventable diseases. Efforts to improve sanitation in coastal areas should involve educational campaigns, infrastructure development, and behavior change interventions tailored to the local context. Keywords: Indonesia, coastal, environment, sanitation, public health